Assessing Air Pollution Crisis in South Asia: The Health, Economic, and Environmental Implications through Case Studies of Lahore, Delhi, and Dhaka - Awez, Jana; Khan, Tayyaba; Ali, Mujeeb (Pakistan Languages and Humanities Review, 2024)
With rapid economic growth, air pollution has become a major concern in South Asia, raising the region to the top of global rankings. The research explored the public health, economic and environmental costs that are related to air pollution in three of South Asia's dirtiest cities: Delhi and Dhaka and Lahore. This study seeks to develop an understanding of the origins and outcomes of significant pollution in these cities, as well as strategies for mitigation. Ground level ozone and particulate matter (PM2. 5). Although the economic development in the region emerged, it did so to the detriment of environmental economics aspects, causing serious health and economic damage. This paper reviews published literature and data including annual PM2.5 Levels from 2014 to 2023 and estimates economic costs of disease based on healthcare use and productivity loss. Dive into select cities - Delhi, Dhaka and Lahore - to explore what air pollution means locally. The results pinpoint that massive surge in air pollution over the last decade, but the economic costs associated are projected to be as high as 1 % of global GDP by 2060. Health effects include increased risk of respiratory diseases and premature death, especially among non-smokers and children. Equally important are the environmental effects, resulting in great loss of biodiversity through local air pollution and global warming. This highlights an immediate requirement to implement strong policy measures focusing on local emission sources and air pollution impacts in various regions. These may include strict emission caps, technological developments as well as public awareness campaigns. Therefore, cross-border co-operation and well-planned development urban policies are essential to cope with this trans boundary matter. They argue that this research will help in understanding the impacts of air pollution crisis in South Asia and provide useful inputs to achieve not only cleaner air & better public health but would be saving economy of the region.